Autophagy promotes ferroptosis by degradation of ferritin. Issue 8 (2nd August 2016) - Hou, Wen; Xie, Yangchun; Song, Xinxin; Sun, Xiaofang; Lotze, Michael T.; Zeh, Herbert J.; Kang, Rui; Tang, Daolin
ABSTRACT: Macroautophagy/autophagy is an evolutionarily conserved degradation pathway that maintains homeostasis. Ferroptosis, a novel form of regulated cell death, is characterized by a production of reactive oxygen species from accumulated iron and lipid peroxidation. However, the relationship between autophagy and ferroptosis at the genetic level remains unclear. Here, we demonstrated that autophagy contributes to ferroptosis by degradation of ferritin in fibroblasts and cancer cells. Knockout or knockdown of Atg5 (autophagy-related 5) and Atg7 limited erastin-induced ferroptosis with decreased intracellular ferrous iron levels, and lipid peroxidation. Remarkably, NCOA4 (nuclear receptor coactivator 4) was a selective cargo receptor for the selective autophagic turnover of ferritin (namely ferritinophagy) in ferroptosis. Consistently, genetic inhibition of NCOA4 inhibited ferritin degradation and suppressed ferroptosis. In contrast, overexpression of NCOA4 increased ferritin degradation and promoted ferroptosis. These findings provide novel insight into the interplay between autophagy and regulated cell death.